Maternal outcomes of magnesium sulphate and diazepam use in women with severe pre-eclampsia and eclampsia in Ethiopia - Kassie GM; Negussie D; Ahmed JH (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Background: Preferred anticonvulsant used to treat and prevent fits in eclampsia currently is magnesium sulphate. Clinical monitoring of tendon reflexes, respiration rate and measuring hourly urine output should be done to ensures safe administration of magnesium sulphate Objective: This study was conducted to evaluate maternal outcomes of magnesium sulphate and diazepam use in the management of severe pre-eclampsia and eclampsia in Jimma University Specialized Hospital. Methods: A retrospective hospital based cross-sectional comparative study was conducted using data collection format. Data was collected from the hospital delivery care register and patient chart records of all pregnant women who presented with the diagnosis of severe pre-eclampsia and eclampsia in two years and three months period from January, 2010 to April, 2012. Data analysis was done by SPSS version 16.0. A P-value of <0.05 was considered statistically significant in all tests. Results: A total of 357 patient charts, 217 from magnesium sulphate and 140 from diazepam treated pregnant women group, were reviewed and analyzed. Three pregnant women from the magnesium sulphate treated group and eleven pregnant women from diazepam treated group had at least one convulsion after taking the drug. Greater proportion of patients in the magnesium sulphate treated group had less than four days postpartum stay as compared to the diazepam treated patients (82.3% versus 66.2%). Seizure occurrence, duration of postpartum hospital stays and birth outcome had a statistically significant association with the type of anticonvulsant used. Conclusions: Magnesium sulphate is more effective than diazepam in the management of severe pre-eclamptic and eclamptic pregnant women in terms of seizure prevention, shortening postpartum hospital stay and reducing maternal morbidities.